2018
DOI: 10.1186/s12936-018-2222-8
|View full text |Cite
|
Sign up to set email alerts
|

Private sector malaria RDT initiative in Nigeria: lessons from an end-of-project stakeholder engagement meeting

Abstract: The malaria rapid diagnosis testing (RDT) landscape is rapidly evolving in health care delivery in Nigeria with many stakeholders playing or having potential for critical roles. A recent UNITAID grant supported a pilot project on the deployment of quality-assured RDTs among formal and informal private service outlets in three states in Nigeria. This paper describes findings from a series of stakeholder engagement meetings held at the conclusion of the project. The agreed meeting structure was a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Thus, it cannot be shown whether the PSCM led to an increase in HH demand, knowledge, and ACT choice over time. Finally, focus here has only been on the market for anti-malarials, but a concern with increased supply and demand of ACT medicines may be their overuse and misuse, both of which contribute to poor treatment outcomes due to misdiagnosis and place undue pressure on the malaria parasite to evolve drug resistance [ 38 40 ]. The increased demand and supply of ACT should be aligned with diagnostic procedures, including what to do upon a negative malaria test.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it cannot be shown whether the PSCM led to an increase in HH demand, knowledge, and ACT choice over time. Finally, focus here has only been on the market for anti-malarials, but a concern with increased supply and demand of ACT medicines may be their overuse and misuse, both of which contribute to poor treatment outcomes due to misdiagnosis and place undue pressure on the malaria parasite to evolve drug resistance [ 38 40 ]. The increased demand and supply of ACT should be aligned with diagnostic procedures, including what to do upon a negative malaria test.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated high proportion of physicians and formal healthcare workers having correct knowledge of diagnosis [11–13] and poor knowledge among PPMVs [14] who usually refer clients to laboratory test. The use of malaria rapid diagnostic test (mRDT) recommended for informal sector including PPMVs is still not well established in Nigeria and was not promoted until recently [15]. Since the PPMVs do not have correct knowledge of diagnostics especially mRDT which is required for prescribing ACT, they are not likely to prefer ACT for treatment of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…In the Nigerian context, one cluster randomized controlled trial had low RDT uptake of just 8% and poor adherence to test results [22]. A later pilot project conducted in three states of Nigeria showed that efforts to increase availability and affordability of mRDTs can increase consumer demand, improve provider pro t margins and con dence in diagnostic provision; however, lessons needed to be learned in terms of, for example, supply chain management, action upon negative test results and ensuring stockages of quality assured test kits, as well as addressing leakage of mRDTs from the public sector [12,23,24]. Given the high prevalence of diagnosis based on experience, an alternative or additional intervention to that of private sector subsidies could be to direct mRDTs for use in self-diagnosis by HH members [25,26]…”
Section: Discussionmentioning
confidence: 99%